2023
DOI: 10.1001/jamaophthalmol.2023.1310
|View full text |Cite
|
Sign up to set email alerts
|

Association of Biomarker-Based Artificial Intelligence With Risk of Racial Bias in Retinal Images

Abstract: ImportanceAlthough race is a social construct, it is associated with variations in skin and retinal pigmentation. Image-based medical artificial intelligence (AI) algorithms that use images of these organs have the potential to learn features associated with self-reported race (SRR), which increases the risk of racially biased performance in diagnostic tasks; understanding whether this information can be removed, without affecting the performance of AI algorithms, is critical in reducing the risk of racial bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Using ML algorithms, comprehensive datasets of health parameters and such associated features as retinal images, electronic health records, and biological markers can be analyzed in an automated, accurate, and efficient manner. For example, AI analysis of retinal images can provide information on age, sex, and race [ 8 10 ]. Similarly, AI algorithms trained on electronic health records can detect patterns and predict 47 systemic biomarkers as outcome variables, including BMI, blood pressure, and HbA1c levels [ 10 ].…”
Section: Retina Photo-based Ai In Evaluating Demographic and Medical ...mentioning
confidence: 99%
“…Using ML algorithms, comprehensive datasets of health parameters and such associated features as retinal images, electronic health records, and biological markers can be analyzed in an automated, accurate, and efficient manner. For example, AI analysis of retinal images can provide information on age, sex, and race [ 8 10 ]. Similarly, AI algorithms trained on electronic health records can detect patterns and predict 47 systemic biomarkers as outcome variables, including BMI, blood pressure, and HbA1c levels [ 10 ].…”
Section: Retina Photo-based Ai In Evaluating Demographic and Medical ...mentioning
confidence: 99%
“…For example, there are fewer Black and Asian DR patients present in ophthalmic care, which is data inequality. 5 In addition, prior studies have shown that retinal anatomy is related to sex and racial information, 18,19 which is an example of data characteristic variability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are fewer Black and Asian DR patients present in ophthalmic care, which is data inequality. 5 In addition, prior studies have shown that retinal anatomy is related to sex and racial information, 18,19 which is an example of data characteristic variability. Mitigating data inequality and addressing data characteristic variability is imperative to reduce performance disparities and achieve more equitable outcomes in deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied in ophthalmology for identifying vision-related diseases [ 2 , 3 ]. However, despite the known racial and ethnic differences in ocular measurements and pathological conditions [ 4 , 5 ], few studies have examined the application of deep learning in different races. Especially the mismatch between training and testing data distribution causes significant degradation in the model performance in multi-ethnic scenarios.…”
Section: Introductionmentioning
confidence: 99%